Use of music and play in pediatric nursing care in the hospital context - Chadi Tondatti, Paula; Correa, Ione (Investigación y Educación en Enfermería, 2012)
Objective. To identify and analyze scientific publications on the use of music and play in pediatric nursing care in the hospital context. Method. In this bibliographic study, papers were sought that were published in Portuguese or English between 2004 and 2009 and included the descriptors: hospitalized child, childhood, child recreation, nursing team, nursing, pediatric nursing, alternatives therapies, music, music therapy, play and playthings, play therapy, playing. For the review, the bibliographic databases used were MEDLINE, ScIELO and LILACS. Results. Seventeen publications were obtained, among which: 59% adopted a quantitative method; mainly nursing developed the activities (88%); per type of article, reviews on the theme and assessments of clinical changes associated with the use of music and play were frequent (59% and 18%, respectively); and the utility of this kind of therapies in nursing care is acknowledged (94%). Conclusion. Play and music are useful therapies that can be used in nursing care for pediatric patients.